Ocean Acidification alters the composition of decapod crustacean communities associated to Posidonia oceanica beds - Zupo, Valerio; Viel, Thomas (BORNH Bulletin of Regional Natural History, 2021)
Ocean Acidification (OA) produces manifest changes in the species assemblages of stable marine ecosystems, although the general levels of biodiversity may be partially conserved. In the case of decapod crustaceans, that represent an interesting taxon because it reacts both to direct and indirect effects of OA, a lowering of pH induces clear changes in the structure of species assemblages. In this study we collected decapod crustaceans at two sites at low pH located at Castello d’Ischia, two control sites at normal pH located at Castello d’Ischia and one external control site. The results confirm that a lower biodiversity characterizes the acidified zones over the year and indicate that key species, normally very abundant in normal conditions all over the year, exhibit impoverished populations associated to the Posidonia oceanica beds off the island of Ischia.